Somatic, hematologic phenotype, long‐term outcome, and effect of hematopoietic stem cell transplantation. An analysis of 97 Fanconi anemia patients from the Italian national database on behalf of the Marrow Failure Study Group of the AIEOP (Italian Association of Pediatric Hematology–Oncology). Issue 7 (24th April 2016) - Svahn, Johanna; Bagnasco, Francesca; Cappelli, Enrico; Onofrillo, Daniela; Caruso, Silvia; Corsolini, Fabio; De Rocco, Daniela; Savoia, Anna; Longoni, Daniela; Pillon, Marta; Marra, Nicoletta; Ramenghi, Ugo; et al.
Abstract : We analyzed 97 Fanconi anemia patients from a clinic/biological database for genotype, somatic, and hematologic phenotype, adverse hematological events, solid tumors, and treatment. Seventy‐two patients belonged to complementation group A. Eighty percent of patients presented with mild/moderate somatic phenotype and most with cytopenia. No correlation was seen between somatic/hematologic phenotype and number of missense mutations of FANCA alleles. Over follow‐up, 33% of patients improved or maintained mild/moderate cytopenia or normal blood count, whereas remaining worsened cytopenia. Eleven patients developed a hematological adverse event (MDS, AML, pathological cytogenetics) and three developed solid tumors. 10 years cumulative risk of death of the whole cohort was 25.6% with median follow‐up 5.8 years. In patients eligible to hematopoietic stem cell transplantation because of moderate cytopenia, mortality was significantly higher in subjects transplanted from matched unrelated donor over nontransplanted subjects, whereas there was no significant difference between matched sibling donor transplants and nontransplanted patients. In patients eligible to transplant because of severe cytopenia and clonal disease, mortality risk was not significantly different in transplanted from matched unrelated versus matched sibling donor versus nontransplanted subjects. The decision to transplant should rely on various elements including, type of donor, HLA matching, patient comorbidities, impairment, and clonal evolution of hematopoiesis. Am. J. Hematol. 91:666–671, 2016. © 2016 Wiley Periodicals, Inc.